GAYA HIDUP WANITA MODERN DALAM KARYA SENI LUKIS - Dra. Jupriani, M.Sn., Yoga Rizki Ananda, Yasrul Sami, S.Sn., M.Sn., (Jurusan Seni Rupa FBS UNP Padang, 2017)
The purpose of creation of this final work is to visualize the lifestyle of the modern woman on the works of contemporary realist painting and to remind the woman now how to choose a modern lifestyle in accordance with the culture and customs in Indonesia. The method for creating this thesis uses five phases: preparation, elaboration stage, the synthesis stage, the stage of realization of the concept and stages of completion. Ten works were lifted tell about lifestyle woman who now is very disturbing, because it does not conform with the customs and cultures that exist in Indonesia.Kata kunci: Modern Women's Lifestyle, Art